X-ray diffraction study and electrical properties of the metal complex Fe(II) including sodium oxalate ligand (Na2C2O4) - Aydogdu, Y; Yakuphanoğlu, Fahrettin; Dagdelen, F; Sekerci, M; Aksoy, I (Elsevier Science Bv, 2002)
The crystal structure, microstructure and electrical properties of the Fe(II) complex including sodium oxalate ligand (Na2C2O4) have been investigated. X-ray diffraction data shows that the sample is triclinic with the cell parameters a = 4.8283 Angstrom, b = 3.9195 Angstrom, c = 12.7633 Angstrom, beta = 97.818degrees and cell volume V = 239.30 Angstrom(3). The do conductivities have been measured as a function of temperature. It is seem that this sample has inorganic semiconductor property. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: complex; sodium oxalate; semiconductor; electrical properties